Clinical characteristics of 248 patients with Krabbe disease: quantitative natural history modeling based on published cases - Komatsuzaki, Shoko; Zielonka, Matthias; Mountford, William K.; Kölker, Stefan; Hoffmann, Georg F.; Garbade, Sven; Ries, Markus (Genetics in medicine, 2019)
Krabbe disease (OMIM 245200) is an orphan neurometabolic disorder caused by a deficiency of the lysosomal enzyme galactocerebrosidase (GALC). Hard clinical endpoints and biomarker-phenotype correlations are useful for future clinical trials. We performed a quantitative analysis of published cases (N = 248) with Krabbe disease, stratified by age at disease onset: early infantile (age 0-6 months), late infantile (age 7-36 months), juvenile/adolescent (age 37-180 months), and adult onset (>180 months). Main outcome measures were age of disease onset and survival. Cerebrospinal fluid (CSF) protein concentrations were explored as a potential predictor of survival. STROBE criteria were respected. Median age of onset was 4 months (early infantile), 14 months (late infantile), 48 months (juvenile), and 384 months (adult). Age of disease onset and therefore disease subtype determined survival rates. CSF protein concentrations predicted age at onset and survival rates in Krabbe disease. Patients with a CSF protein content ≤61.5 mg/dl survived significantly longer than patients with CSF protein values above this threshold. We define the estimated survival in published Krabbe disease cases and demonstrate an association of CSF protein concentration with disease severity. These data inform patient care and clinical trials.
Gesehen am 17.04.2019